Primary Mediastinal HER2-positive Apocrine Carcinoma in Mature Teratoma Treated With Anti-HER2 Therapy and Chemoradiation - SUGIYAMA, KEIJI (In Vivo, 2019)
Background: There are no established guidelines for the management of apocrine carcinomas of the breast; they are treated as a non-specific type of breast cancer. Case Report: We report on the case of a 40-year-old man who developed primary mediastinal apocrine carcinoma overexpressing human epidermal growth factor-2 (HER2). The patient initially underwent complete resection of a mediastinal mature teratoma with a focal apocrine carcinoma component. Two years after surgery, relapse was detected in multiple mediastinal lymph nodes. He received induction chemotherapy including docetaxel, trastuzumab, and pertuzumab; consolidative concurrent chemoradiation was added after six cycles. A complete response was confirmed using computed tomography following this multimodal therapy. After chemoradiation, adjuvant trastuzumab and pertuzumab were administered for 1 year and the patient has since had no evidence of progressive disease. Conclusion: A multi-modal regimen that includes an anti-HER2 agent appears to be a promising treatment for patients with HER2-positive extramammary apocrine carcinoma.